Herbal Medication of Recurrent Aphthous Stomatitis: A Narrative Review - Taufik Septiyan Hidayat; Gofarana Wilar; Nasrul Wathoni (HM Publisher, 2022)
A mouth ulcer or recurrent aphthous stomatitis (RAS) is a mouth mucous tissue inflammation. This disease mainly occurs in patients 10-40 years of age, preferably in women and high socioeconomic backgrounds. The cause of mouth ulcers or RAS could be trauma, infection, digestive problems, or blood disorders. Herbal practitioners widely use herbs, folks, and society to treat various diseases. This research aimed to describe the herbal treatment for RAS. The review results show there are nine plants with the ability to cure RAS, they are Persea americana Mill., Averrhoa bilimbi L., Abrus precatorius Linn., Camellia sinensis (L.) Kuntze., Psidium guajava L., Kaempferia galanga Linn., Aloe vera, Curcuma longa and Citrus hystrix DC. The most parameters used in the studies are clinical trials and in vitro tests.